Factors Explaining Adolescent Girls’ Eating Habits in Urban Benin: A Qualitative Study - MAMA CHABI, Sherifath; Nadia, Fanou; koukoubou, HOUEFFA EUNICE SOREL (My University, 2022)
Adolescence is a period between childhood and adulthood with eating habits often against the nutritional needs of adolescents. The present study used a socio-ecological approach to investigate personal and environmental factors influencing the eating habits of 15- to 19-years old Beninese urban schoolgirls. Eleven focus groups (n = 77) and seven individual interviews were conducted with adolescent girls attending school in Cotonou, Benin. Focus groups were as homogeneous as possible regarding age group and school character. Transcripts were analyzed using an inductive-deductive thematic method using the socio-ecological model. Taste preference for sweet foods, insufficient dietary knowledge and low personal income were factors explaining unhealthy food choices, while higher self-efficacy and healthy outcome expectations mainly characterized their healthy eating habits at the intrapersonal level. Family influence was beneficial for healthy eating while friends’ pressure led to an unhealthy diet at the interpersonal level. At the organizational level, adolescents reported unhealthy school food environments and urban areas increased their unhealthy eating habits. It appears that one factor alone is not enough to influence adolescent girls’ eating habits. Therefore, this study presents the need of elaborating interventions in a school context to improve eating habits in adolescents focusing on different factors in Beninese adolescent schoolgirls.
Keywords: adolescent girls; eating habits; influencing factors; qualitative; school